2016
DOI: 10.1021/acs.est.6b01968
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Roles: An Assessment of Japanese Medaka Estrogen Receptors in Vitellogenin Induction

Abstract: Teleost fish express at least three estrogen receptor (ER) subtypes. To date, however, the individual role of these ER subtypes in regulating expression of estrogen responsive genes remains ambiguous. Here, we investigate putative roles of three ER subtypes in Japanese medaka (Oryzias latipes), using vitellogenin (VTG) I and II as model genes. We identify specific ligand/receptor/promoter dynamics, using transient transactivation assays that incorporate luciferase reporters comprising 3kb promoter/enhancer reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In a two‐tiered testing strategy such as EXTEND2016 program, a reasonable estimation of strength of endocrine disruptive activity on test organisms in vivo, based on the results from preliminary in vitro assay, is helpful for prioritization of test chemicals and prediction of effective concentrations in preparation for Tier 1 and 2 in vivo assays. Teleost fish including Japanese medaka have at least three Esr subtypes and several in vivo and in vitro studies suggested that Esr1 might be the key receptor mediating hepatic VTG gene induction (Lee Pow et al, 2016 ; Mushirobira et al, 2020 ; Nelson & Habibi, 2010 ; Tohyama et al, 2017 ). Therefore, the estrogenic activity determined by the mEsr1 RGA should correlate with the effective concentrations on VTG induction in male medaka in vivo assay.…”
Section: Discussionmentioning
confidence: 99%
“…In a two‐tiered testing strategy such as EXTEND2016 program, a reasonable estimation of strength of endocrine disruptive activity on test organisms in vivo, based on the results from preliminary in vitro assay, is helpful for prioritization of test chemicals and prediction of effective concentrations in preparation for Tier 1 and 2 in vivo assays. Teleost fish including Japanese medaka have at least three Esr subtypes and several in vivo and in vitro studies suggested that Esr1 might be the key receptor mediating hepatic VTG gene induction (Lee Pow et al, 2016 ; Mushirobira et al, 2020 ; Nelson & Habibi, 2010 ; Tohyama et al, 2017 ). Therefore, the estrogenic activity determined by the mEsr1 RGA should correlate with the effective concentrations on VTG induction in male medaka in vivo assay.…”
Section: Discussionmentioning
confidence: 99%
“…In the male SMB in this study, plasma Vtg was positively correlated with vtg and chg , as well as erα , while it was negatively correlated with erβ1. In male zebrafish, erβ was downregulated in response to estrogenic exposures (Reyhanian Caspillo et al, 2014 ; Santos et al, 2014 ), while being upregulated by exposure to antiandrogens (Filby et al, 2007 ) and is involved in plasma Vtg induction in males exposed to estrogenic contaminants (Lee Pow et al, 2016 ). Transcript abundance of erβ1 was significantly correlated with HSI and plasma Vtg in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Vitellogenin (Vtg) is a female-specific protein that was often used as a biomarker of EEs [12,13]. Among fish from which Vtg was derived, the Japanese medaka was recommended as a model organism [14]. Vtg is usually synthesized in the liver of mature female fish under the control of 17β-estradiol (E2), released by liver cells into the bloodstream, transported to the ovaries, and eventually deposited in egg cells and cleaved into lipovitellin (Lv), lecithin (Pv), and other components [15].…”
Section: Introductionmentioning
confidence: 99%